2020
DOI: 10.1016/j.bja.2019.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in professional social media use among anaesthesia researchers

Abstract: Background: Recent studies suggest that female researchers are less visible on social media. The objective of this observational work was to compare the use of professional social networks between male and female anaesthesia researchers. Methods: Among four anaesthesia journals, we analysed the first/last authors (FA/LA) of the most frequently cited articles in 2016e2017 and the authors who published more than one article per year between 2013 and 2018 (prolific authors). We compared the use of the professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 13 publications
3
20
0
1
Order By: Relevance
“…found that the visibility of women remains lower than that of men, particularly on social networks dedicated to science research (e.g., Research Gate). [ 6 ]…”
mentioning
confidence: 99%
“…found that the visibility of women remains lower than that of men, particularly on social networks dedicated to science research (e.g., Research Gate). [ 6 ]…”
mentioning
confidence: 99%
“…Women received lower scientific reputation scores on research social networks (i.e. ResearchGate) compared with men and were significantly less ‘followed’ despite having similar skills and citations [38].…”
Section: Barriers To Women In Researchmentioning
confidence: 99%
“…A social network presence metric that jointly integrates both networks has not been found in the academic literature. All of the authors use as metrics those thrown by each social network [88]. In the case of LinkedIn, presence is measured through the existence of an account, the number of contacts, and the existence of a photo.…”
Section: Model Variablesmentioning
confidence: 99%